Education for a Sustainable Future: The Impact of Environmental Education on Shaping Sustainable Values and Attitudes among Students - Imran, Muhammad; Almusharraf, Norah; Abdellatif, Mohamed Sayed (International Journal of Engineering Pedagogy (iJEP), 2024)
In the face of pressing global challenges, the role of education in shaping sustainable values and attitudes among students has become an urgent priority. This study delves into the immediate impact of education and awareness on students’ knowledge, values, and attitudes toward a sustainable future, with a specific focus on environmental education (EE). It examines various aspects of EE, including curriculum development, teacher training, environmental initiatives within educational institutions, and students’ comprehension of environmental issues. To understand the role of education in fostering a sustainable future, a 2-point Likert scale questionnaire was distributed to a randomly selected sample of 87 high school teachers. The results, analysed through multiple regression analysis, the chi-square test, the t-test, and Cronbach’s alpha value tests, underscore the urgent and significant role of EE in preparing children for a secure future. The study further highlights the increasing urgency and importance of EE in the face of climate change, positioning it as a crucial element for early childhood educational policies.